2012
DOI: 10.1128/jb.01291-12
|View full text |Cite
|
Sign up to set email alerts
|

Directional Evolution of Chlamydia trachomatis towards Niche-Specific Adaptation

Abstract: On behalf of the host-pathogen "arms race," a cutting-edge approach for elucidating genotype-phenotype relationships relies on the identification of positively selected loci involved in pathoadaptation. We studied the obligate intracellular bacterium Chlamydia trachomatis, for which same-species strains display a nearly identical core and pan genome, while presenting a wide range of tissue tropism and ecological success. We sought to evaluate the evolutionary patterns underlying species separation (divergence)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 87 publications
3
38
0
Order By: Relevance
“…We reveal that the overall degree of variation in the amino acid sequences of Inc proteins among strains is similar to that of a characteristic family of C. trachomatis polymorphic proteins (Pmps). Our results strengthen previous studies that suggested that some C. trachomatis Inc proteins could contribute to tissue tropism (8,9,35,43) and confirm recent data suggesting that many inc genes could be under positive selection (8,30). However, almost all of these previous studies analyzed a limited number of sequences, as the majority of the 51 genomic sequences used in our work became available only very recently (25).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We reveal that the overall degree of variation in the amino acid sequences of Inc proteins among strains is similar to that of a characteristic family of C. trachomatis polymorphic proteins (Pmps). Our results strengthen previous studies that suggested that some C. trachomatis Inc proteins could contribute to tissue tropism (8,9,35,43) and confirm recent data suggesting that many inc genes could be under positive selection (8,30). However, almost all of these previous studies analyzed a limited number of sequences, as the majority of the 51 genomic sequences used in our work became available only very recently (25).…”
Section: Discussionsupporting
confidence: 58%
“…3). Moreover, polymorphisms in C. trachomatis genomes are essentially driven by fixation of silent mutations (8). This suggests that the amino acid differences between Inc proteins should not be explained solely by genetic drift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous ompA typing studies have shown that specific genotypes are frequently found in rectal samples from MSM (39)(40)(41)(42), and tissue tropism has been suggested as an explanation (35,(43)(44)(45)(46), mainly based on genetic and cell biological findings. However, recent MLST data show that differing sexual network structures and distributions of C. trachomatis strains in MSM versus heterosexual networks may be an important reason for the findings of certain genotypes in rectum (21).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of positively selected genotypes that align with tissue tropism (ocular, genital, mononuclear/ invasive). For example, in a review of 59 C. trachomatis genome sequences, it was reported that the Tarp gene and the pmp genes have positively selected polymorphisms that cluster significantly with tissue niches (41). Polymorphisms in three distinct open reading frames have been found to associate with rectal but not cervical serovar G isolates, and two further open reading frame polymorphisms were found to associate with rectal and cervical tropism of serovars E, F, and J (42).…”
Section: Chlamydial Genotypes Can Mediate Tissue Tropism and May Be Amentioning
confidence: 99%